2010
DOI: 10.1016/j.ijdevneu.2010.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes in visual cortex of neonatal monocular enucleated rat: a proton magnetic resonance spectroscopy study

Abstract: Neonatal monocular enucleation (ME) is often employed to study the developmental mechanisms underlying visual perception and the cross-modal changes in the central nervous system caused by early loss of the visual input. However, underlying biochemical or metabolic mechanisms that accompany the morphological, physiological and behavioral changes after ME are not fully understood. Male Sprague-Dawley rats (N=14) were prepared and divided into 2 groups. The enucleated group (N=8) underwent right ME (right eye re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 86 publications
4
30
0
Order By: Relevance
“…The brains' response to monocular enucleation in early postnatal life has also been tackled by in vivo Magnetic Resonance Spectroscopy (MRS; Table 1). Three weeks after surgery, Chow and colleagues (2011) found a significant reduction in the Taurine (Tau) and N-acetyl Aspartate (NAA) levels in the visual cortex contralateral to the enucleated eye indicative of neuronal loss and axonal damage (Chow, Zhou et al 2011). Glutamate (Glu), Choline (Cho) and myo-Inositol concentrations were not affected.…”
Section: The Impact Of Age On Neuroplasticitymentioning
confidence: 99%
“…The brains' response to monocular enucleation in early postnatal life has also been tackled by in vivo Magnetic Resonance Spectroscopy (MRS; Table 1). Three weeks after surgery, Chow and colleagues (2011) found a significant reduction in the Taurine (Tau) and N-acetyl Aspartate (NAA) levels in the visual cortex contralateral to the enucleated eye indicative of neuronal loss and axonal damage (Chow, Zhou et al 2011). Glutamate (Glu), Choline (Cho) and myo-Inositol concentrations were not affected.…”
Section: The Impact Of Age On Neuroplasticitymentioning
confidence: 99%
“…In the visual system, recent studies on optic nerve injury and glaucoma indicated that application of brain-derived trophic factor to both the eye and visual cortex resulted in increased levels of retinal ganglion cell survival and function that exceeded those seen following treatment of the eye alone [170]. While the majority of studies on ocular diseases and optic neuropathies focused mainly on the anterior pathways, using localized single-voxel 1 H-MRS at 7 Tesla covering posterior visual brain nuclei, our recent studies indicated its feasibility in detecting alterations in major metabolites (e.g., Cho, glutamate, NAA, taurine, lactate and myo-inositol) in the steady state after complete or partial deafferentation of the anterior visual pathway with reference to creatine (Cr) level [58,[67][68][69]169] (Fig. 4).…”
Section: Evaluation Of Steady-state Metabolisms In Posterior Visual Nmentioning
confidence: 99%
“…In the longitudinal 1 H-MRS study, upon deafferentation of the adult hamster optic tract, a consistent increase in lactate, and a transient decrease in NAA and glutamate followed by a delayed increase in myoinositol were also found in the ipsilesional superior colliculus from 3 days to 4 weeks after lesion compared to the contralateral side [58] (c). (Images modified from [58,67,68]. )…”
Section: Evaluation Of Steady-state Metabolisms In Posterior Visual Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from contributing to visual neuroscience, enucleation as a type of deafferentation can be used to study the balance between neuroprotective 19 and neurodegenerative [20][21][22] properties of the central nervous system. Different procedures to perform enucleation are already described in literature.…”
Section: Introductionmentioning
confidence: 99%